The influence of functional training on biomotor skills in girl tennis players aged 10-12 - OKTAY ZIRHLI; NEVZAT DEMIRCI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪The purpose of this study is to examine whether functional training has an impact on biomotor skills of 10-12-year-old girls. Material and methods: ‪The study involved 20 girls (10 controls and 10 subjects) - who had been playing tennis for at least 2 years. A routine tennis training program was applied to the control group of tennis players participating in the study: 4 days a week, 90 minutes a day for 8 weeks. A 2+2 training program (2 days routine and 2 days functional training) was applied to the experimental group of tennis players for 8 weeks, 4 days a week, 90 minutes a day. At the end of the training program, biomotor tests were conducted. Results: ‪There was not any significant differences when the pre-test and post-test values of the control group of tennis players who performed traditional tennis training were compared with their biomotor skills and Wingate anaerobic power (p> .05). When the pre-test and post-test values of the experimental group of tennis players with 8-week functional tennis training were compared with their biomotor skills and Wingate anaerobic power, a significant difference was found in all variables (p <0.01). Conclusions: ‪The obtained data shows that the "functional training" programs implemented together with "routine tennis training" can positively improve the biomotor characteristics of 10-12 year-old girl tennis players.